Not by bread alone: tough love heals the homeless in South Bend. - Nanni, Louis M. (American Enterprise)
Although homeless shelters were founded on good intentions, they have done more to hurt the homeless than to assist them. Shelters for the homeless offer food and warm lodging to individuals without offering them opportunities to overcome the desperate conditions that are the root causes of their homelessness. In addition, many shelters are so overcrowded and dangerous that many homeless persons choose to sleep outdoors for fear of the violence and vileness inside the shelters. The writer, director of the Center for the Homeless in South Bend, Indiana, describes how his shelter establishes a healthy community atmosphere by combining social science knowledge with equal amounts of religious wisdom, and he outlines the lessons learned from his experience at this center.